Analysis of Business Process Improvement for Mutawwif and Tour Leader Training at Nikmatour Travel Using a Business Process Management Approach - Irham Rusydiharjo; Zahwa Aisya Nabila; Aulia Rahman Ramadhan; Kemas Ibnu Sadid; Raulia Riski; Muhammad Brilliant Agung Wicaksono (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
The Umrah travel industry in Indonesia continues to grow rapidly, driving the need for structured and efficient human resource training standards. However, the training process for Mutawwifs and Tour Leaders (TLs) at Nikmatour Travel is still conducted conventionally, with limited face-to-face sessions, unsystematic distribution of materials, and the absence of an automated evaluation mechanism, resulting in inefficiency and uneven competency among field staff. This study aims to analyze and redesign the Mutawwif and TL training business processes at Nikmatour Travel using a Business Process Management (BPM) lifecycle approach combined with Value-Added Analysis (VAA). Data was collected through observations and semi-structured interviews with management, instructors, and training participants at Nikmatour Travel. The as-is process was mapped using BPMN and analyzed with VAA. The analysis results showed that of the ten as-is activities, four were classified as Non-Value-Adding (NVA), five as Business Value-Adding (BVA), and one as Value-Adding (VA). The designed to-be process integrates an e-learning platform, automated notifications, digital evaluations, and real-time competency monitoring, and successfully eliminates all NVA activities.Quantitative estimates indicate a 44.3% reduction in total cycle time, from 18 hours to approximately 10 hours per training cycle, with an average BVA activity efficiency of 65%.